МЕТИЛИРОВАНИЕ ТОЛУОЛА НА МОДИФИЦИРОВАННЫХ ЦЕОЛИТНЫХ КАТАЛИЗАТОРАХ - А.Т. Масенова; М.К. Калыкбердиев; А.С. Жумаканова; А.С. Сасс; Д.Ш. Касенова (Academic Scientific Journal of Chemistry, 2020)
The toluene methylation reaction can proceed in two directions: 1 – alkylation on the methyl group (in the side chain) with the formation of ethylbenzene, 2 – alkylation on the carbon atom of the benzene ring with the formation of isomeric xylenes. Both reactions attracted the attention of researchers by the possibility of creating of industrial one-stage environmentally friendly, low-energy process for producing valuable monomers from cheaper and more affordable raw materials - styrene and p-xylene, used for the synthesis of polystyrenes and polyethylene terephthalate. During the synthesis of xylenes from toluene, an equilibrium mixture of isomers is formed: para – 23 %, meta – 51 % and ortho – 26 %. To achieve high selectivity for p-xylene, new catalysts based on zeolites with adjustable parameters are needed. Due to the unique structure of the aluminosilicate framework, ZSM-5 zeolite is of great interest for selective para-alkylation, since inside micropores substitution in the o- and m-position should be sterically difficult. A huge role is played by diffusion restrictions, which is favorable for the formation of p-xylene, because the penetration rate of the p-isomer into the porous structure is 3 orders of magnitude higher than that of the o- and m-isomers. As a result of this, the isomeric composition of toluene methylation products depends on the size of zeolite crystals – the longer the diffusion paths, the higher the content of the linear p-xylene isomer. In addition, zeolites of the ZSM type have the highest electronegativity among the zeolites ( 4.2) and exhibit maximum activity in the alkylation of toluene into the aromatic ring, namely, para-selectivity. One of the ways to change the catalytic and molecular sieve properties of zeolites is directed regulation of pores and modification of acid centers by changing the number of acid centers and their nature. The paper presents the results of studies of the conversion of toluene during methylation in the presence of modified catalysts based on synthetic zeolite ZSM-5 with different modules SiO2/Al2O3 35, 80, and 135 which were modified with rare-earth elements (REE) – La, Ce, and Sc. The process was carried out under flowing conditions at the installation "Finetech 4000". It has been studied the following parameters of the process: the effect of the silica modulus of zeolite HZSM-5, the ratio of toluene : methanol, the nature of the modifying metal and the temperature in the range of 250-500°C on the conversion of toluene, the yields of isomeric xylenes and selectivity for p-xylene. It was found that, with the growth of the silica module, the zeolite ZSM-5 from 35 to 135 catalyst activity increases. On the most active zeolite module – 135, the maximum values of toluene conversion are observed 65 %, p-xylene yield 38 % and selectivity 59 %. That is, the higher the zeolite modulus, the higher its activity in the synthesis of pxylene. The optimal composition of the reaction mixture was chosen - the toluene:methanol ratio of 1:3, at which the maximum values of toluene conversion were obtained 65 %, p-xylene yield 38 %, and selectivity for p-xylene 59 %. The selectivity of methylation of toluene to p-xylene increases in the temperature range of 250-500 °C, the maximum values of toluene conversion, yield of p-xylene and selectivity for p-xylene are observed at optimal temperatures of 300-400 °C. Modification of ZSM-5 zeolite with REE (rare earth elements) – La, Ce and Sc increases toluene conversion, yield of the main product and selectivity for p-xylene compared to the initial zeolite. It was found the most active rare-earth metal – La, on which the maximum conversion of toluene reached to 85 %, the yield of p-xylene – 59 %, and the selectivity for p-xylene to 69 %. By activity in para-methylation, metals can be arranged in the following row: La > Ce > Sc. The effect of La, Ce, and Sc, compared with the initial form, is mainly associated with two factors: due to chemical modification, the zeolite channels are narrowed, which leads to an increase of diffusion of pxylene molecules and an increase in steric hindrances for the diffusion of o- and m-xylenes, as well as a decrease in the proportion of strong proton centers on the zeolite surface. Using porosimetry, it was shown that the modification of HZSM-5 reduces pore size: while on pure zeolite, the pore (channel) size was 0.6 nm, then with the introduction of La - 0.4 nm, Ce and Sc – 0.5 nm. This caused the increase in para-selectivity for p-xylene of modified zeolites. In addition, the modification of zeolite changes its surface acidity. The results of thermoprogrammed ammonia desorption showed that rare-earth elements reduce the acidity of strong acid centers, namely, they reduce the ISSN 2224-5286 1. 2020 127 concentration of Brønsted acid centers to 35 % and increase the number of Lewis centers to 28 %, which also increases the selectivity for p-xylene. By X-ray phase analysis, it was shown that the modification does not change the crystal structure of ZSM-5 zeolite. Thus, the high silica module ZSM-5 and the optimum temperature provide an increase in para-selectivity. Of the REE modifiers used, lanthanum exerted the largest para-orienting effect on the activity of ZSM-5 in the toluene methylation reaction and showed the best results: maximum toluene conversion up to 85 %, p-xylene yield up to 59 % and p-xylene selectivity up to 69 %